2001
DOI: 10.1007/s002670010172
|View full text |Cite
|
Sign up to set email alerts
|

Making It Work: Keys to Successful Collaboration in Natural Resource Management

Abstract: This paper explores the positive aspects of collaboration in natural resources. Its purpose was to investigate participants' overall attitudes about keys to successful collaboration. The sample for the study consisted of 671 participants involved in 30 collaborative initiatives (CI) with the Forest Service. Using a mailed questionnaire, this study profiled the collaborative initiatives investigating purpose, problems addressed, groups involved, and years in existence. Respondents were queried on their overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 8 publications
1
60
0
Order By: Relevance
“…Barriers to collaboration include power differentials among stakeholders (Selin and Chavez 1995;Williams and Ellefson 1997), unclear or inflexible legal authorities and administrative policies; organizational cultures unaccustomed to collaborative processes (Cortner et al 1996;Pinchot Institute 2001), agency fears of losing control (Schuett et al 2001), and funding availability (Pinchot Institute 2001). Factors which promote collaboration include shared and open decision-making processes, goal-setting early on in the process, and continual information sharing (Gray 1985;Schuett et al 2001;Williams and Ellefson 1997).…”
Section: Characteristics Of Collaborative Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Barriers to collaboration include power differentials among stakeholders (Selin and Chavez 1995;Williams and Ellefson 1997), unclear or inflexible legal authorities and administrative policies; organizational cultures unaccustomed to collaborative processes (Cortner et al 1996;Pinchot Institute 2001), agency fears of losing control (Schuett et al 2001), and funding availability (Pinchot Institute 2001). Factors which promote collaboration include shared and open decision-making processes, goal-setting early on in the process, and continual information sharing (Gray 1985;Schuett et al 2001;Williams and Ellefson 1997).…”
Section: Characteristics Of Collaborative Processesmentioning
confidence: 99%
“…Barriers to collaboration include power differentials among stakeholders (Selin and Chavez 1995;Williams and Ellefson 1997), unclear or inflexible legal authorities and administrative policies; organizational cultures unaccustomed to collaborative processes (Cortner et al 1996;Pinchot Institute 2001), agency fears of losing control (Schuett et al 2001), and funding availability (Pinchot Institute 2001). Factors which promote collaboration include shared and open decision-making processes, goal-setting early on in the process, and continual information sharing (Gray 1985;Schuett et al 2001;Williams and Ellefson 1997). In addition, stakeholders' willingness to share authority and benefits (Persoon et al 2003), provide resources, acknowledge the legitimacy of other stakeholders, be flexible, and trust other stakeholders increases the likelihood of successful collaborative arrangements (Gray 1985;Schuett et al 2001;Williams and Ellefson 1997).…”
Section: Characteristics Of Collaborative Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, sets of criteria have been developed to analyze the influence of the political, economic, and social context of participation (e.g., Beierle and Konisky 2000). Other frameworks have been developed to evaluate the quality of the participation process (e.g., Webler 1995, Rowe and Frewer 2000, Schuett et al 2001. Result evaluations of individual cases (e.g., ) but also of long-term and large-scale participation approaches have also been carried out (e.g., for an evaluation of the international governance approach in the North American Great Lakes region, see Klinke 2009), as well as meta evaluations based on multiple case studies (e.g., Beierle and Cayford 2002, Jones et al 2009, Newig and Fritsch 2009, Etienne 2010.…”
Section: Trend: Evaluation Of Participationmentioning
confidence: 99%
“…Past research has shown that collaboration also has limitations, however, with many collaborative groups dissolving before accomplishing all of their goals. This can occur for a number of reasons, including time or budgetary limitations, a lack of perceived progress, or a lack of sufficient trust between participants, among others (Wondolleck and Yaffee 2000, Schuett et al 2001, Moote and Becker 2003, Margerum 2011). …”
Section: Introductionmentioning
confidence: 99%